Personal air-conditioning system using evapolar as heat waste management - Ngatiman, Nor Azazi; Mohd Shariff, Abdul Qaiyum; Sutikno, Tole; Wardiyono, Suparje; Manap, Mustafa; Jopri, Mohd Hatta (Institute of Advanced Engineering and Science, 2021)
Air-conditioning system that uses compressor-based initiate more energy and affects bill rate. As a result, an application of the Peltier impact module, a portable air-conditioning system is introduced to compensate user convenience by lowering sensible and latent heat inside the office area. Thermoelectric Peltier module is a thermoelectric semiconductor that offers cooling and hot plate once the plate is supplied by electric. The result reduces the cost, power consumption, and give thermal comfort in a dedicated space. The advantage of the study is the ability to cost deduction due to low power consumption and green technology devices factor because without refrigerant that harms the environment. Redesign the product with evapolar as heat waste management affect the performance and need to be validated. The development stage of this product is better compared to a previous product which offers small scale, light, and portable. This product focuses on the office room, which gives a good feeling to users. This product uses air to remove the heat waste and the result indicates evapolar is fit enough in dissipating heat. Finally, the performance of this system developed demonstrated that it can attain thermal comfort level.